Soil microbial population as affected by tillage and rice cultivation modes in Stagnic Anthrosols and Lateritic Red Earth soils in Southern China - Asenso, Evans; Wang, Zhimin; Kai, Tian; Li, Jiuhao; Hu, Lian (Frontiers in Soil Science, 2022)
Microbial population (MP) is considered to be relatively important part of soil health, quality, and productivity. Therefore, this study aimed to access the effects of tillage and rice cultivation modes on soil MP in Stagnic Anthrosols and Lateritic Red Earth soils. The treatments were: (i) T1: land tilled twice with moldboard plow and hill-seeding of pregerminated seeds with direct seeding machine of 4-6 seeds per hill at a planting space of 25×15 cm, (ii) T2: land tilled twice with rotary tiller and hill-seeding of pregerminated seeds with direct seeding machine of 4-6 seeds per hill at a planting space of 25×15 cm, (iii) T3: land tilled twice with moldboard plow and seedlings of 15-day-old were mechanically transplanted with transplanting machine, at a transplanting hill of 4-6 seedlings at a transplanting space of 25×15 cm, and (iv) T4: land tilled twice with rotary tiller and seedlings of 15-day-old were mechanically transplanted with transplanting machine, at a transplanting hill of 4-6 seedlings and a transplanting space of 25×15 cm. Findings showed that T1 improved the MP and increases rice yield. T1 showed a high increase in MP, and the rice productivity of 32.81% (1H) and 13.91% (2H), and 16.48% (1H) and 18.13% (2H) for Zeng-Cheng and Yi-Yang respectively (1H: 1st harvest, and 2H: 2nd harvest). In conclusion, T1 was found to be better in improving MP and increasing rice yield and could be adopted as a suitable approach for improving soil health, quality, and productivity.